10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
We report a 36-year-old woman who presented with acute visual hallucinations, delusions, and dizziness 2 months after uncomplicated kidney transplantation. Brain magnetic resonance imaging (MRI) revealed T2/FLAIR hyperintensities in the dorsal pons and bilateral temporal cortices, atypical yet consistent with PRES. Tacrolimus-induced PRES was diagnosed in the absence of severe hypertension or other precipitants. Tacrolimus was discontinued and replaced with cyclosporine, with complete clinical resolution and normalization of MRI findings within 8 weeks. This case underscores the importance of prompt clinical suspicion and discontinuation of tacrolimus in transplant recipients with neuropsychiatric symptoms and supportive neuroimaging, even with atypical lesion distribution. Close therapeutic drug monitoring and rapid immunosuppressant adjustment can facilitate full recovery and prevent permanent sequelae.